Предмет: Математика,
автор: Аноним
докажите что значение выражения не зависит от x
Приложения:
![](https://files.topotvet.com/i/464/464f6811d81b0b32cd5304d485052e14.jpg)
Ответы
Автор ответа:
0
эта задача наполовину правильная
6*(2-1.5x)+3*(3x-2)=12-9x+9x-6=6 не зависит от х
8*(0.5х-3)-2*(5-2х)=4x-24-10+4x=8x-34 зависит от х
6*(2-1.5x)+3*(3x-2)=12-9x+9x-6=6 не зависит от х
8*(0.5х-3)-2*(5-2х)=4x-24-10+4x=8x-34 зависит от х
Похожие вопросы
Предмет: География,
автор: angelasos2010
Предмет: История,
автор: kamenevoleg6
Предмет: Биология,
автор: Аноним
Предмет: Физика,
автор: saig
Предмет: Литература,
автор: 0анге